Prognostic impact of the length of the longitudinal resection margin in colon cancer. (July 2017) - Lee, S. Y.; Kim, C. H.; Kim, Y. J.; Kim, H. R.
Abstract: Aim: Although several guidelines recommend a longitudinal resection margin (LRM) of at least 5 cm, the impact of the LRM on survival is still unknown. The study assessed the prognostic significance of the LRM in patients with colon cancer. Method: We retrospectively reviewed 1343 primary colon cancer patients without distant metastasis who underwent curative resection between January 2004 and December 2012. Patients were classified into three groups: LRM < 3 cm ( n  =   186), LRM ≥ 3 and <5 cm ( n  =   376) and LRM ≥5 cm ( n  =   781). Clinicopathological characteristics and the oncological outcome in the three groups were compared. Results: The median LRM length was 5.0 cm (range 0.5–26.0 cm). With increasing LRM, the number of retrieved lymph nodes (LNs) tended to increase (19.5 ± 12.0, 22.1 ± 12.8 and 30.0 ± 16.2; P  <   0.001). After a median follow‐up period of 45 (1–128) months, 3‐year disease‐free survival (DFS) (89.2%, 89.0% and 87.0%; P  =   0.629) and 5‐year overall survival (OS) (89.0%, 92.1% and 91.8%; P  =   0.679) were not significantly different between the three groups. When confounders were adjusted, LRM was not significantly associated with either DFS or OS, but the number of retrieved LNs (< 12) was an independent risk factor for both DFS (hazard ratio 1.748, 95% confidence interval 1.048–2.917) and OS (hazard ratio 1.929, 95% confidence interval 1.046–3.559). Conclusion: LRM was not associated with oncological outcome, but care should be taken to obtain an adequate number of LNs for better survival.